Auditor political connections and SEC oversight - Krishnan, Jagan; Li, Meng; Park, Hyun Jong (Contemporary Accounting Research, 2025)
Abstract We examine whether auditor political connections are associated with the SEC's oversight of audit clients . Specifically, we test whether auditors' political action committee contributions are associated with three SEC oversight actions: comment letters, investigations, and Accounting and Auditing Enforcement Releases (AAERs). Consistent with higher political connections inducing heightened scrutiny from the SEC, we find that the clients of auditors with higher political connections are more likely to receive comment letters and face SEC investigations. However, conditional on SEC investigation, we find no association between auditor political connections and the issuance of AAERs. We consider heightened attention from investors and analysts toward audit clients as one possible mechanism leading to increased SEC scrutiny because auditor political connections could be perceived as a red flag. Using EDGAR downloads and the number of earnings forecast revisions, we document evidence consistent with the existence of this mechanism. These findings add to our understanding of how auditor political connections could influence SEC oversight over audit clients.